Optimizing radiology remote reading: leveraging technology to improve efficiency. - Al-Katib, Sayf; Dearden, Andrew; Al-Bassam, Noor; Ghannam, Jacob; Beydoun, Ali; Kolderman, Nathan; Nandalur, Reyna; Nandalur, Kiran (Abdominal Radiology, 2025)
Remote work has been increasingly utilized in the profession of radiology over recent years. Setting up your individual workstation offers an opportunity to tailor it to suit your preferences without the restriction of a universal setup to accommodate multiple users. Important considerations when setting up a home workstation include selecting the optimal work location, choosing the proper desk and chair, and configuring an ideal computer monitor layout. The use of peripheral devices, such as programmable mice and hands-free dictation tools can improve efficiency and reduce repetitive strain injuries. This article also explores the use of smart home devices and programmable scripts using AutoHotKey to further streamline workflow and maximize the benefits of a remote workstation.